ANALISIS PERAN PENDIDIKAN KEWIRAUSAHAAN DAN MEDIA SOSIAL DALAM MENUMBUHKAN MINAT WIRAUSAHA MAHASISWA PROGRAM STUDI MANAJEMEN, UNIVERSITAS SARJANAWIYATA TAMANSISWA YOGYAKARTA - Agus Dwi Cahya; Lisa Anis Sawitri; Kadek Isna; Yuli Endar Yani (PERFORMANCE: Jurnal Bisnis & Akuntansi, 2021)
This study aims to determine whether there is an effect of entrepreneurship education and social media on the entrepreneurial interest of students in the Management Study Program, Faculty of Economics, Sarjanawiyata Tamansiswa University, Yogyakarta. Entrepreneurship is one of the compulsory courses for UST FE Management students. This course is expected to foster an entrepreneurial spirit in students so that students are interested in running their own business when they graduate. Meanwhile, social media provides information including about entrepreneurship which can also attract students' interest in entrepreneurship. The results of the research on the t test show that the entrepreneurial education variable (X1) has a positive and significant effect on the entrepreneurial interest variable (Y) with a value of 0.003 and the social media variable (X2) also has a significant effect on entrepreneurial interest (Y) with a value of 0.000. In the F test, entrepreneurship education and social media simultaneously affect entrepreneurial interest which is indicated by a significance value of 0.000. Keywords: Entrepreneurship Education, Sosial Media, Entrepreneurial Interest